1987
DOI: 10.1002/ajmg.1320270422
|View full text |Cite
|
Sign up to set email alerts
|

New autosomal dominant branchio‐oculo‐facial syndrome

Abstract: We observed an autosomal dominant disorder of abnormal upper lip, which resembles a poorly repaired cleft lip, malformed nose with broad bridge and flattened tip, lacrimal duct obstruction, malformed ears, and branchial cleft sinuses and/or linear skin lesions behind the ears in several persons in 3 families. In each of the 3 families, an affected parent had at least one affected child. Father-to-son transmission in one of these families ruled out X-linked inheritance. Other anomalies include coloboma, microph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
5

Year Published

1989
1989
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 4 publications
1
44
0
5
Order By: Relevance
“…Although these defects were pres ent in some form in most (42/45, 93%) of typically affected probands who had either a cervical or supraauricular defect, they were absent in patient 5 of Fujimoto et al [1987], and the grandmother reported by Muller and Kobelt [1991], i.e., patient 10 in this report.…”
mentioning
confidence: 46%
See 4 more Smart Citations
“…Although these defects were pres ent in some form in most (42/45, 93%) of typically affected probands who had either a cervical or supraauricular defect, they were absent in patient 5 of Fujimoto et al [1987], and the grandmother reported by Muller and Kobelt [1991], i.e., patient 10 in this report.…”
mentioning
confidence: 46%
“…A typical, excluded Legius et al, 1990 Fielding andFryer, 1992 H in g e t al., 1992 Harrison, 1957Farm er and M axm en, 1960Schweckendieck et al, 1977Lee et al, 1982H a ll et al, 1983Tom et aL, 1985Fujimoto et al,, 1987Barr et al, 1989Givi et al, 1989Dado and Gonzalez-Crussi, 1989 L in et a l, 1991 Mazzone et al, 1992L in et al, 1992Schmerler et al, 1992Baie and S oteloA vila, 1993Baie, 1994 McCool andWeaver, 1994 New Total …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations